PREVALENCE OF BACTERIAL LOADS ON SOME FRESH VEGETABLES SOLD IN LOCAL MARKET OF BHOPAL - JHILI SARKAR*, RAGINI GUTHALWAL; NIDHI TRIPATHI (The Journal of Research ANGRAU, 2021)
Vegetables are nutritious, sources of vitamins, minerals, fibres and these are part of our daily diet. However, main problem is quality of fresh vegetables available in the markets. It is important to detect and identify the microbial flora especially enteropathogens associated with fresh vegetables. Microbial analysis was performed on five different types of vegetable samples viz., egg plant (brinjal) (Solanum melongena), bottle gourd (Lagenaria siceraria), capsicum (Capsicum annuum), carrot (Daucus carota), spinach (Spinacia oleracea) which were randomly collected from the local markets of Bhopal city. Vegetables showed the presence of more than four predominating pathogenic bacteria. Common bacteria found were identified as Serratia entomophila, Proteus vulgaris, Yersinia aldovae, Enterobacter aerogenes with Enterobacter genera being more dominating. Characteristic growth on selective cum differential media confirmed the presence of mixed Enterobacteriaceae population and the members were identified based on their biochemical properties. The presence of heavy load of Gram negative bacteria in fresh vegetables showed poor quality which puts a question mark on its wholesomeness. The presence of Enterobacteriaceae reflects the existence of favourable conditions in respective vegetables for the growth of microorganisms.